A New Polyketide from the Endophytic Fungus Penicillium chermesinum - Cici Darsih; Vilailak Prachyawarakorn; Chulabhorn Mahidol; Somsak Ruchirawat; Prasat Kittakoop (Universitas Gadjah Mada, 2017)
A new polyketide derivative, 2-chloro-3,4,7-trihydroxy-9-methoxy-1-methyl-6H-benzo[c]chromen-6-one (1), was isolated from the endophytic fungus Penicillium chermesinum. The structure was established on the basis of UV, IR, HR-ESI MS, and 1D and 2D NMR experiments. The cytotoxicity against four cancer cell lines (HuCCA-1, HepG2, A-549, and MOLT-3) of compound 1 are 14.94-115.71 µM.